PENGARUH PERPUTARAN MODAL KERJA DAN PERPUTARAN KAS TERHADAP RETURN ON ASSETS PADA PT KALBE FARMA TBK PERIODE 2014-2023 - Annisa Nurul Afiah; Muhamad Restu Wijaya (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The purpose of this study was to determine the effect of Working Capital Turnover and Cash Turnover on Return On Assets at PT Kalbe Farma Tbk for the 2014-2023 Period, both partially and simultaneously. The object of this research is PT Kalbe Farma Tbk, with secondary data taken from annual financial reports during the 2014-2023 period. The research method used is quantitative method, with data collection techniques through the time series data method. Data analysis was carried out using descriptive methods, classical assumption tests, simple linear regression tests, multiple linear regression tests, correlation coefficient tests, determination coefficient tests, and hypothesis tests processed using the SPSS (Statistical Product and Service) version 25 application. The results of this study indicate that partially, Working Capital Turnover has no significant effect on Return On Assets with a tcount value (2,197) < t table (2,365) and a significance value (0.059 > 0.05). While Cash Turnover partially has a significant effect on Return On Assets, with a tcount value (4,254)> t table (2,365) with a significance value (0.003 <0.05). Simultaneously, Working Capital Turnover and Cash Turnover have a significant effect on Return On Assets, with a value of Fcount (8.972) > Ftable (4.74) with a significance value of (0.012 < 0.05). The Adusjted R-Square coefficient of determination shows that 63.9% of the variation in Return On Assets can be explained by these two variables, while 36.1% is influenced by other variables outside this study.